Peningkatan Kompetensi Pengelola Rumah Tinggal Mahasiswa Berbasis Pendidikan Karakter dan Solusi Praktis Masalah Sosial Mahasiswa - Sarmini .; Anna Noordia; Gading Gamaputra; Lisnani .; Hezron Sabar Rotua Tinambunan; Suyanti Fatma Umayfa; Ika Febriana Wati (Universitas Negeri Surabaya, 2026)
Surabaya State University Campus 5 was established in 2024 and has 16 study programs with a total of 2,888 students from various regions. This campus provides a great opportunity for the community to build a residence in the form of boarding houses. Based on data from the Magetan Regency government, the number of rooms owned to date is 1,642 rooms spread across several local sub-districts and villages. These communities built boarding houses according to their own initiative without going through the licensing process, so there are different variants for each boarding house. They do not yet have rules and regulations that students must follow and the boarding house managers do not yet have the skills to do as boarding house managers. Problems faced related to boarding house management include social issues for students that require special handling, the lack of socialization to boarding house managers by the district government, diverse views from boarding house managers in managing their boarding houses, limited abilities in character education that must be carried out, and minimal ability to solve problems caused by students. The implementation methods used include providing workshops, lectures and role-playing methods, workshops and mentoring, and seminars. The results of this activity, namely the rules and SOPs for boarding house managers, can be a practical solution in maintaining harmony between the interests of the campus and the community, especially student boarding house managers and the government, especially student boarding house managers. Keywords: boarding house management, character education, practical solutions, rules and regulations, social problems.